Video Assisted Learning Analysis in Improving Student Learning Outcomes in ElementarySchools - Wahyu Sri Lestari; Sunardi Sunardi; Eka Budhi Santosa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
This research investigates the use of video as a medium of learning in elementary grades. Video media is an appropriate and accurate learning media in conveying messages and will greatly help students' understanding. With video media, students will understand more about the material presented. In particular, this study aims to explore whether video-assisted learning can increase student motivation. A qualitative approach was adopted in this study by employing teachers and students in an elementary school in Indonesia as research participants. These participants were selected purposively. Interviews, observations, and documentation were used to collect data. This study found that video-assisted learning media positively facilitates technology-enhanced teaching and learning processes and offers more optimal time management, flexible and varied teaching materials. These findings also show that the use of video-assisted learning media has a positive impact on student learning. Videos can create variations in class so that students' attention is focused on learning which stimulates students' motivation to be involved during the teaching and learning process. Students are motivated to take part in learning because the materials and media used are more sophisticated, modern, interesting, effective and innovative.